Pelaksanaan Ritual Usahatani Padi Sawah pada Subak Kawasan Perkotaan dan Kawasan Perdesaan Kasus: Subak Ayung, Desa Buduk, Kecamatan Mengwi dan Subak Sulangai, Desa Sulangai, Kecamatan Petang, Kabupaten Badung - DEWA PUTU ARTAJAYA; I NYOMAN SUTJIPTA; I DEWA PUTU OKA SUARDI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Implementation of Rice Farming Ritual at Subak of Urban and Rural Areas Case: Subak Ayung at BudukVillage Mengwi District and Subak Sulangai at Sulangai Village District of Petang Badung RegencyCultural diversity provides vivid colors in every area as a tradition that characterizes each tribe in Indonesia. Bali historically has had a tradition, culture, and religious commitment in the form of an organization called Subak. The belief of Subak members in conceiving land as Mother Nature, water as a symbol of Lord Vishnu, and rice as Goddess Sri strengthens the existence of Hinduism-based Subak cultural wisdom. Implementation of ritual activities in the paddy rice farming in Subak of urban and rural areas is not known with certainty. Based on these descriptions, it is interesting to note the implementation and ritual differences of rice farming of Subak in urban and rural areas. The aim of research was to determine the implementation and ritual differences of rice farming on the Subak Ayung and Subak Sulangai. The sampling method was done by using quota sampling, each with 50 respondents. The key informants were pekaseh (Subak head) and management of Subak Ayung and Subak Sulangai. Implementation of ritual activities in paddy rice farming in Subak near urban areas the case of Subak Ayung with the average achievement, the percentage score of 66.50% in the medium category and Subak Sulangai amounted to 72.85% belonging to the frequent/ good category. Subak of rural areas tended to have better ritual implementation compared with Subak of urban areas by a margin of 6.35%. Based on the results of the study, it is expected that Subak Ayung and Subak Sulangai members are more frequent / better to perform rituals of paddy rice farming so as to preserve the culture of Subak.